The Intellectual History of Entrepreneurship Education in Indonesian Higher Education - Imam Shofwan; Sunardi Sunardi; Abdul Rahman; Gunarhadi Gunarhadi (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: Entrepreneurship education in Indonesia did not emerge as a sudden response to contemporary economic challenges, but rather evolved through a long, intellectual, and policy-driven process shaped by historical, political, and socio-cultural dynamics. While existing studies predominantly focus on the effectiveness and outcomes of entrepreneurship education, relatively little attention has been paid to its historical and intellectual foundations. This study addresses this gap by examining the intellectual history of entrepreneurship education in Indonesian higher education. Using a qualitative historical approach combined with discourse analysis, the study analyzes primary sources, including education policies, curriculum regulations, and official government documents, alongside secondary academic literature from the 1980s to the present. The findings reveal that entrepreneurship education gradually shifted from a marginal development discourse during the late New Order period to a formally institutionalized component of higher education following the Reformasi era, particularly through the National Education System Law of 2003 and subsequent curriculum reforms. This trajectory reflects a broader paradigm shift from a bureaucratic education model toward one emphasizing innovation, self-reliance, and an entrepreneurial mindset, further reinforced by the Merdeka Belajar–Kampus Merdeka policy. The study contributes to the historiography of education by contextualizing entrepreneurship education within Indonesia’s intellectual, ideological, and policy landscape, highlighting the importance of historically grounded perspectives for evaluating current and future educational reforms. Abstrak: Pendidikan kewirausahaan di Indonesia tidak muncul sebagai respons yang tiba-tiba terhadap tantangan ekonomi kontemporer, melainkan berkembang melalui proses panjang yang bersifat intelektual dan digerakkan oleh kebijakan, serta dibentuk oleh dinamika historis, politik, dan sosial-budaya. Sementara kajian-kajian yang ada lebih banyak berfokus pada efektivitas dan capaian pendidikan kewirausahaan, perhatian terhadap fondasi historis dan intelektualnya masih relatif terbatas. Penelitian ini mengisi celah tersebut dengan mengkaji sejarah intelektual pendidikan kewirausahaan dalam pendidikan tinggi di Indonesia. Dengan menggunakan pendekatan historis kualitatif yang dipadukan dengan analisis wacana, penelitian ini menganalisis sumber-sumber primer berupa kebijakan pendidikan, regulasi kurikulum, dan dokumen resmi pemerintah, serta literatur akademik sekunder sejak dekade 1980-an hingga masa kini. Temuan penelitian menunjukkan bahwa pendidikan kewirausahaan secara bertahap bergeser dari wacana pembangunan yang bersifat marginal pada akhir masa Orde Baru menjadi komponen yang terinstitusionalisasi secara formal dalam pendidikan tinggi pasca era Reformasi, khususnya melalui Undang-Undang Sistem Pendidikan Nasional Tahun 2003 dan berbagai reformasi kurikulum setelahnya. Trajektori ini mencerminkan pergeseran paradigma yang lebih luas, dari model pendidikan yang birokratis menuju model yang menekankan inovasi, kemandirian, dan pola pikir kewirausahaan, yang semakin diperkuat melalui kebijakan Merdeka Belajar–Kampus Merdeka. Studi ini berkontribusi pada historiografi pendidikan dengan menempatkan pendidikan kewirausahaan dalam lanskap intelektual, ideologis, dan kebijakan pendidikan Indonesia, serta menegaskan pentingnya perspektif historis dalam mengevaluasi reformasi pendidikan masa kini dan masa depan.